2016
DOI: 10.2147/ijn.s97541
|View full text |Cite|
|
Sign up to set email alerts
|

Increased radiosensitivity of colorectal tumors with intra-tumoral injection of low dose of gold nanoparticles

Abstract: The potential of gold nanoparticles (GNPs) as radiosensitizers for the treatment of malignant tumors has been limited by the large quantities of GNPs that must be administered and the requirement for low-energy X-ray irradiation to optimize radiosensitization. In this study, we enhance the radiosensitivity of HCT116 human colorectal cells with tiopronin-coated GNPs (Tio-GNPs) combined with a low-energy X-ray (26 keV effective energy) source, similar to the Papillon 50 clinical irradiator used for topical irrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 41 publications
1
23
0
1
Order By: Relevance
“…To treat deep tumors, a radioactive source may have to be encapsulated inside a gold nanoparticle (i.e., in a gold nanocage) [219]. Furthermore, if DNA specificity cannot be achieved in patients, successful treatment may still be possible by intratumor injection of GNPs, as recently shown by Shi et al [220] and Bobyk et al [204].…”
Section: Interaction Of Lees With Dna Bound To Gold Nanoparticlesmentioning
confidence: 99%
“…To treat deep tumors, a radioactive source may have to be encapsulated inside a gold nanoparticle (i.e., in a gold nanocage) [219]. Furthermore, if DNA specificity cannot be achieved in patients, successful treatment may still be possible by intratumor injection of GNPs, as recently shown by Shi et al [220] and Bobyk et al [204].…”
Section: Interaction Of Lees With Dna Bound To Gold Nanoparticlesmentioning
confidence: 99%
“…Indeed, GNPs have been shown to enhance the sensitivity of HCT116 cells to 26 keV X-rays with a sensitizer enhancement ratio (SER) of 1.69 in vitro. 10 However, megavoltage X-rays are widely used instead of kiloelectronvolt sources in clinical practice. It has been reported that GNPs exhibit efficacy using megavoltage radiation sources in breast, prostate, and lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The enhancement of radiation damage and the biological effects, associated with the individual physical and chemical properties of Pt-CAs and GNPs, have been observed in several in vitro and in vivo studies [23][24][25][26][27][28][29][30][31][32][33][34][35][36]. However, from the results obtained individually with GNPs and Pt-CAs, it became obvious that combining both radiosensitizers in a common carrier could considerably enhance the benefit of chemoradiation therapy (i.e., GNPs produce large quantities of LEEs that would strongly react with any Pt-CAs bound to DNA or other biomolecules vital for cell survival).…”
Section: Introductionmentioning
confidence: 97%
“…Tumor response was determined in immunodeficient NU/NU nude mice with carboplatin as the CA. According to recent results, the limitation of radiotherapy in colorectal cancer treatment [25] could be improved through the use of a liposomal formulation carrying both a CA and radio enhancer. Preliminary results are concisely presented in this article on this novel method of combining metal nanoparticles with CAs in an effort to enhance the benefits of concomitant chemoradiation therapy.…”
Section: Introductionmentioning
confidence: 99%